Reading Comprehension and Metalinguistic Knowledge in Chinese Readers: A Meta-Analysis - Dong, Yang; Peng, Shu-Na; Sun, Yuan-Ke; Wu, Sammy Xiao-Ying; Wang, Wei-Sha (Frontiers in Psychology, 2020)
Metalinguistic knowledge has a facilitative effect on reading comprehension. This meta-analysis examined the relationship between metalinguistic knowledge and reading comprehension among Chinese students. By focusing on both Chinese and English scripts’ reading comprehension performance, this study synthesized 46 studies with 73 independent samples that represented 10,793 Chinese students from primary school to university levels. We found that, in both Chinese and English scripts’ reading, morphological awareness had the strongest correlation with reading comprehension, whereas both phonological awareness and orthographical skill had a similar medium correlation with reading comprehension. All three metalinguistic knowledge, which was not significantly influenced by the selected moderators of grade group, area, language type, and assessment, had an independent correlation with reading comprehension. The results suggested that reading stages did not significantly impact the function of metalinguistic knowledge on both Chinese and English scripts’ reading comprehension for Chinese students’. In addition, for Chinese students, morphological awareness plays a more important role than phonological awareness and orthographical awareness in both Chinese and English scripts’ reading comprehension.